2020. - Honold, Alexander. (Walter de Gruyter GmbH, 2020)
The Yearbook of the German Schiller Society is an annual journal that primarily publishes essays on German-language literature from the Enlightenment to the present day. This time span coincides with the collections housed at the German Literary Archive in Marbach, which is under the stewardship of the German Schiller Society. Although studies on Schiller are especially welcome, they constitute only a portion of the journal's spectrum.